A Novel Porcine Model of Bilateral Hindlimb Bypass Graft Surgery Integrating Transit Time Flowmetry - Andrew B. Haymet; Cora Lau; Christina Cho; Sean O’Loughlin; Nigel V. Pinto; David C. McGiffin; Michael P. Vallely; Jacky Y. Suen; John F. Fraser (Journal of Cardiothoracic Surgery)
Abstract Background Bypass graft surgery is a key surgical intervention for ischemic heart disease (coronary bypass graft surgery) and critical limb ischemia (peripheral bypass graft surgery). Graft occlusion remains a significant clinical problem for both types. Further research into the pathobiological mechanisms of graft occlusion are needed in order to design targeted therapeutic strategies. Methods Three Large White female pigs (mean weight 52.3 +/- 4.4 kg) received general anaesthesia prior to surgery. The external jugular vein was harvested bilaterally, and a bilateral femoral peripheral arterial bypass was performed, with the superficial femoral artery permanently ligated. The grafts were interrogated immediately post operatively on-table using Medistim MiraQ transit time flowmetry system (Medistim, Oslo, Norway) to assess graft performance. On postoperative day three, the pigs were returned to the operating room, and the grafts were interrogated once again using transit time flowmetry. Results Six out of six (100%) successful bilateral EJV to femoral artery bypass grafts were performed. All pigs were successfully recovered, and returned to the operating room at postoperative day 3. The wounds were re-opened and the grafts were inspected. Postoperative graft assessment was performed with transit time flowmetry using the Medistim MiraQTM system (Medistim, Oslo, Norway), demonstrating all grafts were patent (100%). Conclusion This model may serve as a platform to gain further mechanistic insight into graft failure pathobiology. By combining a bilateral graft model with gold-standard transit time flowmetry, longitudinal experimentation of targeted therapeutic interventions to combat graft failure may be further studied with improved objectivity.